Effectiveness of a Nurse-Led Intensive Home-Visitation Program for First-Time Teenage Mothers (Building Blocks): A Pragmatic Randomized Controlled Trial. Issue 5 (May 2016) - Robling, Michael; Bekkers, Marie-Jet; Bell, Kerry; Butler, Christopher C.; Cannings-John, Rebecca; Channon, Sue; Corbacho Martin, Belen; Gregory, John W.; Hood, Kerry; Kemp, Alison; Kenkre, Joyce; Montgomery, Alan A.; et al.
Abstract : Abstracted from Lancet 2016;387:146–155 Individual, social, and economic circumstances faced by teenage mothers can challenge a successful start for children and interrupt mothers' long-term socioeconomic stability. The Family-Nurse Partnership (FNP) is a licensed intensive home-visiting intervention developed in the United States and introduced into practice in England.